2007
DOI: 10.1001/archpsyc.64.12.1435
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Drug Problems in Young Adults Exposed to Trauma and Posttraumatic Stress Disorder

Abstract: Association of PTSD with subsequent incident drug use disorders remained substantial after statistical adjustment for early life experiences and predispositions reported in previous studies as carrying elevated risk for both disorders. Posttraumatic stress disorder might be a causal determinant of drug use disorders, possibly representing complications such as attempts to self-medicate troubling trauma-associated memories, nightmares, or painful hyperarousal symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
76
2
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(90 citation statements)
references
References 63 publications
8
76
2
3
Order By: Relevance
“…Consistent with prior studies of trauma exposure and PTSD, elevated rates of parental problem drinking (Dube et al, 2001;Fergusson et al, 1996b;Sher et al, 1997), MDD (Breslau et al, 1997;Hapke et al, 2006;Kendler et al, 2000;McCutcheon et al, 2009), CD (Afi fi et al, 2009Fu et al, 2007;Kessler et al, 1995;Koenen et al, 2002), regular smoking (Al-Mamun et al, 2007;Breslau et al, 2003;Nelson et al, 2006), and cannabis abuse (Duncan et al, 2008;Kilpatrick et al, 2000;Nelson et al, 2006;Reed et al, 2007) were observed in women who had experienced traumatic events-both those who developed PTSD and those who did not-compared with women who did not report any trauma exposure. Much of the prior research in this area has involved comparing rates of co-occurring psychopathology and psychosocial risk factors in individuals with PTSD with those who do not meet diagnostic criteria, without regard to the trauma exposure status of individuals in the non-PTSD group or, conversely, comparing traumaexposed with non-trauma-exposed individuals, without regard to the PTSD status of individuals in the traumaexposed group.…”
Section: Association Of Posttraumatic Stress Disorder and Trauma Withsupporting
confidence: 76%
See 1 more Smart Citation
“…Consistent with prior studies of trauma exposure and PTSD, elevated rates of parental problem drinking (Dube et al, 2001;Fergusson et al, 1996b;Sher et al, 1997), MDD (Breslau et al, 1997;Hapke et al, 2006;Kendler et al, 2000;McCutcheon et al, 2009), CD (Afi fi et al, 2009Fu et al, 2007;Kessler et al, 1995;Koenen et al, 2002), regular smoking (Al-Mamun et al, 2007;Breslau et al, 2003;Nelson et al, 2006), and cannabis abuse (Duncan et al, 2008;Kilpatrick et al, 2000;Nelson et al, 2006;Reed et al, 2007) were observed in women who had experienced traumatic events-both those who developed PTSD and those who did not-compared with women who did not report any trauma exposure. Much of the prior research in this area has involved comparing rates of co-occurring psychopathology and psychosocial risk factors in individuals with PTSD with those who do not meet diagnostic criteria, without regard to the trauma exposure status of individuals in the non-PTSD group or, conversely, comparing traumaexposed with non-trauma-exposed individuals, without regard to the PTSD status of individuals in the traumaexposed group.…”
Section: Association Of Posttraumatic Stress Disorder and Trauma Withsupporting
confidence: 76%
“…There is an extensive literature linking AUDs to CD (King et al, 2004;Kuperman et al, 2005;McGue et al, 2001) as well as smoking (Cardenal and Adell, 2000;Dawson, 2000;Grucza and Bierut, 2006) and cannabis abuse and dependence (Degenhardt et al, 2002;Grant and Pickering, 1998;Stinson et al, 2006). Evidence for elevated rates of cannabis and other illicit drug use disorders in individuals with PTSD is also strong (Breslau et al, 2003;Kilpatrick et al, 2000;Perkonigg et al, 2000;Reed et al, 2007), with the odds of meeting criteria for illicit drug abuse or dependence ranging from two to four times that in those without PTSD (Breslau et al, 1997;Chilcoat and Breslau, 1998;Kilpatrick et al, 2000). Similar fi ndings have been reported for nicotine dependence (Breslau et al, 2003;Perkonigg et al, 2000).…”
mentioning
confidence: 55%
“…An association between stress and an increased risk of abusing addictive substances already is well established (56)(57)(58)(59)(60). For example, chronic stress has been shown to be a strong predictor of addiction vulnerability (58), and posttraumatic stress disorder is closely associated with an increased incidence of nicotine, alcohol, and other drug abuse (60).…”
Section: Figurementioning
confidence: 99%
“…In a study of young adults, Reed, Anthony, and Breslau (2007) found that traumatic experiences were associated with excess risk for substance abuse or dependence only if mediated by the occurrence of post-traumatic stress disorder (PTSD). A substantial amount of research has confirmed a close relation between PTSD and SUD, suggesting that 30–60% of individuals seeking help for SUD meet the criteria for lifetime PTSD (Brady, McCauley, & Back, 2015).…”
Section: Introductionmentioning
confidence: 99%